2015
DOI: 10.1161/strokeaha.114.007797
|View full text |Cite
|
Sign up to set email alerts
|

Bright Vessel Appearance on Arterial Spin Labeling MRI for Localizing Arterial Occlusion in Acute Ischemic Stroke

Abstract: 564S everal studies have demonstrated that arterial spin labeling (ASL)-perfusion-weighted imaging (PWI) can detect hypoperfusion and perfusion-diffusion mismatch in the setting of acute stroke, with good to modest correlation to dynamic susceptibility contrast perfusion MRI. [1][2][3][4] Recently, ASL-PWI has been incorporated as a part of the acute ischemic stroke evaluation in our institution, and with its increasing use, we have encountered patients with acute ischemic stroke in whom a characteristic brigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…9 ABS can also be seen without an occlusion and may then be because of a stagnant flow upstream of a stenosis. Our data are in agreement with the recent work of Yoo et al, 10 which highlights that the bright intravascular signal, attributable to slowflowing blood on ASL imaging, may facilitate the detection and localization of arterial occlusion in acute IS. The authors moreover affirm that 10 occlusions could solely be detected by the ASL bright vessel appearance, whereas no occlusion case could be exclusively identified by the susceptibility vessel sign on susceptibility weighted imaging.…”
Section: Majer Et Al Use Of Raw Asl Data In Patients With Ischemic Stsupporting
confidence: 93%
See 1 more Smart Citation
“…9 ABS can also be seen without an occlusion and may then be because of a stagnant flow upstream of a stenosis. Our data are in agreement with the recent work of Yoo et al, 10 which highlights that the bright intravascular signal, attributable to slowflowing blood on ASL imaging, may facilitate the detection and localization of arterial occlusion in acute IS. The authors moreover affirm that 10 occlusions could solely be detected by the ASL bright vessel appearance, whereas no occlusion case could be exclusively identified by the susceptibility vessel sign on susceptibility weighted imaging.…”
Section: Majer Et Al Use Of Raw Asl Data In Patients With Ischemic Stsupporting
confidence: 93%
“…The authors moreover affirm that 10 occlusions could solely be detected by the ASL bright vessel appearance, whereas no occlusion case could be exclusively identified by the susceptibility vessel sign on susceptibility weighted imaging. In accordance with these observations, we found that the ABS had a high sensitivity (100% in our study compared with 94% for Yoo et al 10 ). However, unlike them, occlusions assessed by EPI T2* showed less sensitivity than susceptibility weighted imaging in our patient sample.…”
Section: Majer Et Al Use Of Raw Asl Data In Patients With Ischemic Stsupporting
confidence: 92%
“…The postlabeling delay (time between labeling and readout) is set to be longer than the arterial transit time; therefore, all blood has entered the tissue and no blood remains visible in large vessels (Alsop et al, 2015). However, due to pathological changes and also to anesthesia, blood flow velocities might slow down and blood potentially remaining inside the vessels can be misinterpreted as areas of elevated perfusion (overshoot) (Yoo et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This bright vessel sign corresponds to an accumulation of protons in labelled arterial blood immediately upstream from the arterial occlusion. The sensitivity of the bright vessel sign would be superior to that of the susceptibility vessel sign [3638]. The bright vessel sign can also reveal certain distal arterial occlusions not initially detected on the vascular sequences, e.g.…”
Section: Arterial Spin Labellingmentioning
confidence: 99%
“…The bright vessel sign can also reveal certain distal arterial occlusions not initially detected on the vascular sequences, e.g. 3D TOF sequences [38].
Fig.
…”
Section: Arterial Spin Labellingmentioning
confidence: 99%